SYNTHESIS AND EVALUATION OF DIAMINO SUBSTITUTED 1,3,4 THIADIAZOLE AS POSSIBLE BOMBYX MORI GROWTH ENHANCER - UMADEVI PARIMI,; VENU GOPAL REDDY B,; ANITHA MAMILLAPALLI, (International Journal of Pharma and Bio Sciences, 2012)
Sericulture or silk farming is the rearing of silkworms for the production of raw silk. The mulberry silkworm, Bombyx mori, is a domesticated and monophagous insect which feeds only on the leaves of mulberry for its nutrition. Thiadiazoles are heterocyclic compounds containing oxygen and nitrogen. 1, 3, 4, thiadiazoles are extensively studied and are known to play diverse biological activities. Diamines or polyamines are found in various biological fluids and are necessary for optimal growth, replication and metabolism of every cell in the body. This report describes the synthesis of diamino substituted thiadiazole and its effect on the growth parameters of Bombyx mori silk worm. Results show that the title compound at high concentration resulted in increased worm weight, silk gland weight and cocoon weight and at low concentrations proved to be beneficial for improving the pupal weight. We conclude that the synthesized compound can be fed to B. mori silk worms for improving their economic parameters.